Análise da ação administrativa em cooperativas agropecuárias do triângulo mineiro: um estudo de multi casos - Rodrigues, Maria de Lourdes (2005)
This study had the aim to analize administrative actions in mixed-farming cooperatives, considering the well-being promotion for their associates. Besides, was considered the hypothesis that the social results are not disclosed in a right way. The subject was chosen because the importance of the cooperativism likes an association model. The technique of research chosen to develop this job was the multi cases studies, were where researched four mixed-farming cooperatives, all of them work with “milk goods”. These cooperatives are located in Minas Gerais State, specifically in Triângulo Mineiro region. The research consisted in identificating the cooperatives’ administrative actions, considering four categories: organization size, social actions, Services offers and the social results’ disclosure. Firstly a bibliographical review about third sector, cooperativism and Social Audit was carried out. Afterwards was necessary to define which cooperatives would be studied. The criterion used for that choice was the OCEMG’s classification, where the cooperatives are classified by region and Net Worth amount. After the choice, was made a local research, with interviews, non-participant observation and documents analyses. Taking the dates into, were used documental analyses techniques, because the study was based on qualitative technical approach. The facts shown that the cooperatives defend the associate economical interests, since they (the cooperatives) take available structure and Services to this proposal. As for the social objectives, it is necessary to emphasize that they are not enough to assure the associate’s participation and management. Considering the transparency in social actions’ disclosure, the research revealed that the studied cooperatives do not prepare the Social Audit, not even systematize social actions in reports. However, some progress was identified as for the amount of resources purposed do DAC, since this amount does not limited itself to the FATES’ resources; the technical assistance’s maintenance, even in period where losses were verified and the concerning about associate and employers’ education. The study made possible to list the following aspects: instead of the fragilities, the cooperativism is still an interesting association model; the mixed-farming cooperatives are extremely important to the rural development; the disclosure of the social actions will happen as the cooperatives to become aware of the value of such information; and it is relevant to the associate to change your point of view about your participation in the cooperatives.